Forests Perspectives and Land Use Changes (Sustainability in Debate, 2014)
Emilio Moran. Meio Ambiente & Florestas. São Paulo: Editora Senac São Paulo, 2010. 224 p.Série Meio Ambiente; 11. Tradução Carlos Slak. ISBN 978-85-7359-999-2.